(untitled) (Journal of the College of Basic Education, 2023)
The twentieth century witnessed a set of technological transformations in all fields, which were accompanied by changes in the quality of pollutants in the natural and urban environment, and became like noise invading our planet without mercy, even rural areas are nostalgic for the calm that has been absent from them irrevocably, so man has become more vulnerable to various types of radiation and harmful waves that are not The visual effects caused by the elements used in the interior space, therefore anxiety, insomnia and psychological pressure dominated the daily behavior of people, penetrating into the community life and within the same family. The first chapter contained the research problem that emerged through the following question: "Is the study of interior space designs according to the Stoic philosophy important in terms of the func tional and aesthetic data of the university library spaces whose design is based on this system that achieves design balance?" The aim of the research was determined: to reveal the materialistic tendency of the Stoic philosophy and the possibility of creating comfortable designs for the users of the interior space.